Sustainability reporting and transitory environmental sustainability risks in manufacturing - Daniel Schneider; Alexander Schüler; Markus Woerle; Dominik Schneider; Niklas Eisold; Gunther Reinhart (International Journal of Sustainable Engineering)
This study critically examines sustainability reporting within Germany’s mechanical and plant engineering sector, focusing on the alignment with European Sustainability Reporting Standards (ESRS) and the disclosure of essential environmental metrics. Through a methodical assessment of 329 companies statistically representative for the sector, the research uncovers significant variations in reporting practices and a general shortfall in meeting ESRS requirements, especially in key environmental aspects. Methodologically, the research integrated a thorough analysis of public sustainability reports alongside a direct collection of data to evaluate the scope and depth of reporting. The findings reveal that while some companies are actively engaging in comprehensive sustainability reporting, a majority display considerable gaps, particularly in disclosing critical environmental information. This study highlights the need for enhanced transparency and robust reporting mechanisms to address and mitigate transitory environmental risks faced by the sector. By bridging these reporting gaps, companies could better align with regulatory expectations and stakeholder demands, thus safeguarding their operational viability and competitive edge in an increasingly regulated market. The insights gained underscore the challenges companies face in adapting to stringent sustainability standards, emphasising the strategic necessity of proactive engagement in sustainability reporting practices.